Evaluation Broadcasting Video Signals by Wireless Network Parameters between Client/Server. - Azzat, Media S.; Erçelebi, Ergun (Science Journal of University of Zakho, 2015)
This paper focuses on designing and implementing a system for recently emerging video transmission by wireless networks parameters. Such parameters are considering packet loss rate, bandwidth and delay, as well as the quality of server (QoS), which eventually contributed to the user’s the quality of experience (QoE). The signals of the captured video by cameras send to the server-host then to be displayed and broadcasted to the client-host. This system overcomes the several problems as: delay, packet loss rate and bandwidth by resources and destinations through controlling the permissions and broadcasting, as well as to the monitoring the configuration of the system during broadcasting. The advantage of this system is to improve application software to be used in a friendly use with as maximum as possible of flexibility and full optional controlling to get complete features of the video broadcasting systems. The system controls the problems of delay, loss rate and bandwidth between source and destination, through controlling the permissions, broadcasting and monitoring when configuration of the system during broadcasting. The synchronization between two sides of the wireless network was achieved when incoming signals from the cameras to the server-side and broadcasting these signals to the client-side. Eventually this system enables the administrator to monitor the dataflow from server-side to client-side and apply compressing with many compression techniques on the incoming and broadcasted signals.